Case Report: Endovascular electrothrombosis treatment for carotid cavernous fistula caused by ruptured primitive trigeminal artery aneurysm - Wan, Yuhui; Cheng, Zengjing; Lu, Ziyan; Yang, Dehong; Li, Zhaoliang; Yang, Kai; Chen, Binglin; Chen, Ailin; Zhu, Qing (Frontiers in Surgery, 2025)
Aneurysms of a persistent trigeminal artery (PTA) are exceptionally uncommon, and their rupture leading to a carotid-cavernous fistula (CCF) is even more extraordinary. The contemporary management of CCF predominantly revolves around endovascular approaches, with a variety of techniques such as detachable balloons or coils, coil embolization augmented with Onyx adhesive, and stent grafting. Herein, we report a successful intervention in a patient with a CCF instigated by a ruptured PTA aneurysm, employing a combination of detachable coils and endovascular electrothrombosis, yielding favorable outcomes.